Developing Future Health Professionals’ Capacities for Working With Aboriginal and Torres Strait Islander Peoples - Hendrick, Antonia; Britton, Katherine Frances; Hoffman, Julie; Kickett, Marion (The Australian Journal of Indigenous Education, 2014)
This article details reflections of an interdisciplinary team of educators working with groups of health sciences students in preparing them for working with Aboriginal and Torres Strait Islander peoples. The first-year common core unit discussed here is one attempt to equip future health practitioners with skills and knowledges to work adequately in this complex area. Processes of engagement, central to critical reflection and learning that is iterative and cyclical, are emphasised here using the authors’/educators’ experiences of teaching in the unit. Within this first-year unit, the content delivered — its underlying processes and principles, and assessment design using reflective journalling — coalesces into what is a valued unit of study in preparing students for practising in this field. While the content of the unit is political, provocative and powerful, which presents challenges for students and teaching staff alike, we maintain here that processes of critical reflection and action learning are central to its success and significantly contribute to enhancing students’ learning and to changing students’ perspectives.